La fiscalidad de las cooperativas desde la perspectiva de la internacionalización de la economía social y el desarrollo sostenible - Patón García, Gemma (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
The economic crisis has created a major concern in developedcountries for control of social risks with negative effects on growth and this problem can be approached from the perspective of Corporate Social Responsibility (CSR). Thus, CSR is seen as an entrepreneurial attitude aimed at promoting social, economic and environmental purposes while guarantying competitiveness in the international market. Thus, social economy can contribute to sustainable development, economic and social cohesion, to promote productive and income distribution, to ensure employment and equality of opportunities. The purpose of this study is to have an influence onthe role that taxation plays in the area of incentive policies related to social economy and very prominently manifested in the legal status of cooperatives. The approach aims to provide proposals on tax regulation of cooperatives taking the perspective of the international context and the size of the sector in countries like Spain and Peru in order to encourage cooperative social responsibility. Indeed, the importance of providing a legal and fiscal framework to promote their internationalization connects providentially with the principles that govern the cooperative action. We consider that it is essential, from the perspective of sustainable development and cooperatives’social responsibility, to take into account in the tax regime applicable criteria that can be justified on constitutional principles, the general interest of society or internationalization economic activity. Also, there could be other positive effects in the area of Latin America, such as decreasing tax evasion and the formalization of at least a portion of the informal sector of the economy, including the real impulse to CSR.

La crisis económica ha generado una mayor preocupación en los países desarrollados por el control de los riesgos sociales con efectos negativos sobre el crecimiento y este problema puede abordarse desde la perspectiva de la Responsabilidad Social de las Empresas (RSE). De este modo, la RSE se observa como la actitud empresarial dirigida a promover fines sociales, económicos y ambientales a la vez que garantizar la competitividad en el mercado internacional. Así, la economía social puede contribuir al desarrollo sostenible, a la cohesión económica y social, a fomentar el tejido productivo y la distribución de la renta, a favorecer el empleo y a procurar la igualdadde oportunidades. El presente estudio pretende incidir en el papel que la fiscalidad desempeña en el área de la incentivación de políticas relacionadas con la economía social y que muy destacadamente se manifiesta en el régimen jurídico de las cooperativas. El enfoque adoptado persigue aportar propuestas para la regulación fiscal de las cooperativas considerando el contexto internacional y la dimensión del sector en países como España y Perú en aras de incentivar la llamada «responsabilidad social cooperativa». En efecto, la importancia de ofrecer un marco legal y fiscal de promoción de su internacionalización se cohonesta de forma providencial con los principios que gobiernan la acción cooperativista. Consideramos que es indispensable, desde la perspectiva del desarrollo sostenible y la responsabilidad social de las cooperativas, que se tome en consideración en el régimen fiscal aplicable criterios que puedan justificarse en los principios constitucionales, el interés general de la sociedad o de internacionalización de la actividad económica. Asimismo, podrían conseguirse otros efectos positivos en el área de América Latina como la disminución de la evasión fiscal y la formalización de al menos una parte del sector informal de la economía, e incluso el impulso a la auténtica RSE.
Taxation of cooperatives from the perspective of international expansion and sustainable development of social economy
Keywords: Fiscalidad; Desarrollo sostenible; Responsabilidad social empresarial; Crisis económica; Régimen de cooperativas; Economía social; https://purl.org/pe-repo/ocde/ford#5.05.00